Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The impact of using smart applications, “Sehaty application”, on health care at primary Care Center in Al-Qurayat region Mrs. Manal Abdulrhaman Ajina 2. The impact of management transparency in promoting organizational loyalty – Field study on staff at The National Centre for Environmental compliance Mr. Badr Faisal Al-Ghamdi 3. The impact of the application of comprehensive quality standards on the performance of hospitals in The Kingdom of Saudi Arabia Mrs. Maysa Ehsan Tayb 4. The Role of Talent Management Practices in Promoting the Creative Behavior: A Field Study on the Employees of the Saudi Electricity Company in Asir Mr. Turki Aziz Abdullah Al Shumaylah, Co-Prof. Faisal Ahmed Abed Shuaibi 5. The new international orientation towards a multipolar world: China and Russia as a model Mrs. Noura Ali Abdallah 6. Testing the Relationship Between the Real Estate Market Index and the Saudi Stock Market Index for the Period from 2015 AD - 2022 AD Mr. Ammar Suliman Fallatah, Asst-Prof. Haitham Zaker Khoj, Co-Prof. Hatem Khaled Akeel 7. Monetary Policy and Stock Market Return: The Case of Saudi Arabia Interest Rates hikes and Stocks Returns Dr. Somaiyah Fahad Alalmai, Lecturer Alyaa Talal AlGhanmi